2015
DOI: 10.1097/bsd.0b013e31828d003d
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Surgical Outcomes Including Preoperative Total Knee Replacement and Knee Osteoarthritis Status in Female Patients With Lumbar Spinal Stenosis

Abstract: A poor preoperative functional score, the presence of preoperative KOA, and longer operational levels were shown to be poor prognostic factors for the 1-year surgical outcome of LSS. Also, patients in the TKR group showed the worst ODI scores at preoperative and postoperative 1-year evaluations. Consideration of these factors when planning for spine surgery could be helpful in predicting the surgical outcomes of lumbar spinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
0
17
1
Order By: Relevance
“…Consistent with our results, Ho et al reported that the presence of preoperative KOA was a poor prognostic factor for 1-year surgical outcomes of LSS. 11 However, because the past study used a single HRQOL parameter, the details of poor prognosis have remained unclear. In the present study, multiple HRQOL analysis revealed that the postoperative outcomes of the VAS for buttocks and lower limbs and SF-36 domains of physical functioning, role physical, and vitality were significantly worse in LSS patients with KOA than in LSS patients without KOA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, Ho et al reported that the presence of preoperative KOA was a poor prognostic factor for 1-year surgical outcomes of LSS. 11 However, because the past study used a single HRQOL parameter, the details of poor prognosis have remained unclear. In the present study, multiple HRQOL analysis revealed that the postoperative outcomes of the VAS for buttocks and lower limbs and SF-36 domains of physical functioning, role physical, and vitality were significantly worse in LSS patients with KOA than in LSS patients without KOA.…”
Section: Discussionmentioning
confidence: 99%
“…Ho Lee et al investigated surgical outcomes of LSS patients with or without KOA using the Oswestry Disability Index (ODI) and demonstrated that the presence of preoperative KOA was a poor prognostic factor for surgical outcomes of LSS. 11 However, because they assessed surgical outcomes using a single self-reported health-related quality of life (HRQOL) questionnaire, no definitive conclusions could be drawn. Therefore, by using multiple HRQOL parameters, this study aimed to investigate how the KOA condition affects the surgical outcome of lumbar spinal surgery for LSS patients.…”
mentioning
confidence: 99%
“…In our study, the preoperative score of SRS pain and function significantly improved in both groups at the ultimate follow-up. However, group I showed [23], at postoperative 1 year, ODI scores were shown to be affected by the operational level, the preoperative ODI, and the presence of advanced radiographic knee OA (Kellgren/Lawrence grades III and IV) (P < 0.05). This phenomenon was also supported in the study of the relationship between clinical outcomes and sagittal radiographic parameters by Lafage et al [24].…”
Section: Discussionmentioning
confidence: 86%
“…These results indicate that clinical prognosis after spinal fusion surgery may be unfavorable if severe knee OA in patients exists concurrently. According to the report of Ho et al [23], at postoperative 1 year, ODI scores were shown to be affected by the operational level, the preoperative ODI, and the presence of advanced radiographic knee OA (Kellgren/Lawrence grades III and IV) (P<0.05). This phenomenon was also supported in the study of the relationship between clinical outcomes and sagittal radiographic parameters by Lafage et al [24].…”
Section: Discussionmentioning
confidence: 97%